The Impact of Intercultural Exchange on Secondary School Exchange Students and Their Host Families - Sustarsic, Manca (Journal of International Students, 2020)
The last decade has seen a significant increase of international student mobility and a growing popularity of secondary school exchange programs in the United States and around the world. Drawing upon culture learning theory, the purpose of this study is to understand the impacts, challenges, and rewards of intercultural exchange on secondary school exchange students and their host families. I performed a case study of in-depth interviews with six students who were placed in Hawai’i for an academic year on the Kennedy-Lugar Youth Exchange and Future Leaders Exchange merit-based scholarships, as well as interviews with their volunteer host families. Findings show that intercultural exchange occurs as a two-way process. Both students and host families reap the benefits of intercultural exchange by way of active interaction and culture sharing that is enhanced by a positive student–host relationship.